Three-level atoms in a radiation field: population of atomic levels and atomic squeezing - Reboiro, Marta (2008)
The transfer of spin between atoms and a radiation field is formulated in an algebraic model. The system is composed of three-levels atoms in interaction with a radiation field. The appearance of atomic squeezing when the photon sector of the initial state consists of a squeezed photon state is analysed. It is found that atomic squeezing depends not only on the initial state but also on the interaction couplings and the number of atoms of the system.